SERVQUAL model applied to higher education public administrative services - Mauri Cesar Soares (Brazilian Journal of Operations & Production Management, 2017)
Objective: This article aims to report the application of the SERVQUAL model in a public higher education institution from the student body's perspective, in order to assess the Quality of administrative services. Methods: The SERVQUAL Model, which was developed by Parasuraman Zeithaml and Berry, was applied and the "expectation" and the "perception" of respondents were evaluated, resulting in Perceived Quality. Results: The results show that, between five proposed and evaluated dimensions in the Model, the "tangibility" was the only one with positive results. Limitations: The study took place in a Brazilian public higher education unit, whose results cannot be considered to all units. Data were collected by the student body, since these services are exclusively provided to them. Originality/value: The use of the SERVQUAL method to evaluate services provided by education institutions is not trivial, thus their analysis can collaborate with managers in preparing the unit strategic planning as well as demonstrating that the method can be used by other institutions wishing to evaluate the quality of services offered to their students.